Histological evaluation of decellularized skeletal muscle tissue using two different decellularization agents - Hrebíková, Hana; Voborníková, Magda; Hetešová, Milada; Mokrý, Jaroslav (Acta Medica, 2016)
The aim of the present study was to determine effect of two decellularized agents, sodium dodecyl sulphate (SDS) and Triton X-100, to the skeletal muscle tissue. Final scaffold was evaluated by several histological techniques to analyse preservation of essential structures including collagen and elastic fibres, basement membranes, glycosaminoglycans and also to confirm elimination of nuclear and cytoplasmic components which are redundant in effectively prepared decellularized scaffolds. Comparison of tissue scaffolds processed with different detergents proved that SDS is superior to Triton X-100 as it can effectively decellularize muscle tissue.
Keywords: Coloring Agents; Glycosaminoglycans; dodecylsíran sodný; glykosaminoglykany; Microscopy; Muscle, Skeletal; kolagen; Sodium Dodecyl Sulfate; Surface-Active Agents; elastická tkáň; kosterní svaly; Octoxynol; Animals; Elastic Tissue; mikroskopie; povrchově aktivní látky; barvicí látky; zvířata; Collagen; Tissue Scaffolds; myši; oktoxynol; tkáňové podpůrné struktury; Mice